Heterojunction photodetector based on graphene oxide sandwiched between ITO and p-Si - Ahmad, Harith; Tajdidzadeh, Mojgan; Thandavan, Tamil Many K. (Taylor & Francis, 2018)
The drop casting method is utilized on indium tin oxide (ITO)-coated glass in order to prepare a sandwiched ITO/graphene oxide (ITO/GO) with silicon dioxide/p-type silicon (SiO2/p-Si) heterojunction photodetector. The partially sandwiched GO layer with SiO2/p-Si substrate exhibits dual characteristics as it showed good sensitivity towards the illumination of infrared (IR) laser at wavelength of 974 nm. Excellent photoconduction is also observed for current–voltage (I–V) characteristics at various laser powers. An external quantum efficiency greater than 1 for a direct current bias voltage of 0 and 3 V reveals significant photoresponsivity of the photodetector at various laser frequency modulation at 1, 5 and 9 Hz. The rise times are found to be 75, 72 and 70 μs for 1, 5 and 9 Hz while high fall times 455, 448 and 426 are measured for the respective frequency modulation. The fabricated ITO/GO-SiO2/p-Si sandwiched heterojunction photodetector can be considered as a good candidate for applications in the IR regions that do not require a high-speed response.